The Effectiveness of WHO Stress Management in Reducing Distress Among Parents as Caregivers of Children With Neurodevelopmental Disorders - Alifiani Nurrohmah; Gusti Ayu Maharatih; Vitri Widyaningsih (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2025)
Background: Caring for a child with neurodevelopmental disorders presents a significant challenge for caregivers, often resulting in stress, emotional pressure, and disruption in family and work life. To support the mental health and well-being of caregivers, effective interventions are needed to manage stress. This study was conducted to evaluate the effectiveness of stress management recommended by WHO in reducing stress levels among caregivers of children with neurodevelopmental disorders. Subjects and Method: The research was conducted using an experimental research design, pre-test and post-test design without a control group. The study was conducted at the Disability Service and Inclusive Education Center of Surakarta City in April-May 2024. A total of 103 participants completed the questionnaire, with 74 meeting the inclusion criteria (PSS score > 14). The dependent variable was distress measured using the PSS questionnaire. The independent variable was WHO Stress Management. Data were analyzed using the Wilcoxon test and multivariate linear regression. Results: The majority of caregivers were female (91.9%) with a mean age of 37.89 years (SD=6.2). The results showed that the mean PSS score decreased significantly from 19.14(SD=3.06) at pre-test to 17.51 (SD=3.23) at post-test (p <0.001). The level of moderate stress decreased from 97.3% to 90.5%, and the level of severe stress decreased to 0% (p=0.003). Family income (p=0.000), caregiving support (p=0.001), and compliance in listening to audio (p <0.001) variables significantly influenced the reduction in PSS scores. Conclusion: The WHO stress management intervention is effective in reducing distress among parents caring for children with neurodevelopmental disorders.